1976
DOI: 10.1128/iai.14.1.290-297.1976
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of guinea pig transfer factor released into plasma

Abstract: Plasma fractions and plasma dialysate from 2,4-dinitrochlorobenzeneand tuberculin-sensitive guinea pigs that had been treated with either antilymphocytic serum or normal control serum were analyzed for their ability to transfer lymphocyte transformation, passive cutaneous anaphylaxis, and macrophage migration inhibition, as well as delayed hypersensitivity in vivo. Antilymphocytic serum caused rapid release of material, which has characteristics of transfer factor, into the plasma. It was dialyzable, migrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It was also reported that DTH could be transferred by dialyzable transfer factor of leukocytes (39) or immune-serum (40). Many investigators support the hypothesis that several T cell factors (41,42) and idiotypic antibody (43,44) act in DTH regulation in mice.…”
Section: ) Grmentioning
confidence: 93%
“…It was also reported that DTH could be transferred by dialyzable transfer factor of leukocytes (39) or immune-serum (40). Many investigators support the hypothesis that several T cell factors (41,42) and idiotypic antibody (43,44) act in DTH regulation in mice.…”
Section: ) Grmentioning
confidence: 93%